Migração venezuelana no Brasil e mediações comunicacionais: um estudo a partir das tecnicidades, espacialidades e temporalidades - Dainezi, Gustavo Fernandes Americo (2023)
This thesis presents the construction of a procedural approach that articulates the mediations of the fourth Barberian map, the theories of procedurality and migratory networks, the oral report, the cartographic approach, and accompaniment of digital profiles. We seek to understand how the social uses of ICTs and the formation of networks by Venezuelan immigrants in Brazil are configured in relation to the mediations of temporality, spatiality and technicality. To do so, based on a qualitative methodology, we conducted 13 semi-structured interviews with 10 Venezuelan immigrants and monitored the participants’ profiles on social media. From the ten narratives created, we obtained numerous clues, among which we highlight the protagonism of the diaspora and migratory networks – created and activated by the participants – in this migration defined as happening in a context of crisis; the presence of Social Assistance in mediating access to the right to communications in these trajectories and the absence of the internet and the smartphone during a significant part of the trajectories. Our approach also enabled the de-localization of central analysis concepts.